PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA KARTU KUARTED UNTUK MENINGKATKAN HASIL BELAJAR IPAS PESERTA DIDIK KELAS VC SDN MANYARAN 01 SEMARANG: PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA KARTU KUARTED UNTUK MENINGKATKAN HASIL BELAJAR IPAS PESERTA DIDIK KELAS VC SDN MANYARAN 01 SEMARANG - Nova Amalia; Ika Ratnaningrum; Aprilia Nur Fitriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
students in science subjects because they were considered boring subjects. The aim of this research is to determine whether there is an increase in science learning outcomes through the application of the problem based learning model assisted by quartered card media in class V C students at SDN Manyaran 01 Semarang. The research subjects used were 28 class V C students at SDN Manyaran 01 Semarang, consisting of 15 male students and 13 female students. This research uses a Classroom Action Research (PTK) design. This research was carried out in two cycles through four stages, namely, planning, implementing actions, observing and reflecting. Data collection techniques used in this research include observation, tests and documentation. The data analysis techniques used are descriptive qualitative and quantitative. The results of research in cycle I showed that the number of students who achieved completeness was 17 with a percentage of 61% and 11 students who did not complete it with a percentage of 39%. In cycle II there was an increase with 25 students achieving completeness with a percentage of 89% and 3 incomplete students with a percentage of 11%. The average increase in students' science learning outcomes in pre-cycle and cycle II through the N-Gain test was 0.71 in the medium category. Based on these results, it can be concluded that the use of the problem based learning model assisted by quartered card media can improve the science learning outcomes of class VC students at SDN Manyaran 01 Semarang.